Hepatitis E Infection With Acute Liver Failure. Issue 3 (18th March 2020) - Phan, Timothy; Desmond, Christopher
ABSTRACT: A 21-year-old man from India presented with acute hepatitis associated with a 1-week history of abdominal pain, pruritus, and dark urine. Over a 7-day admission, the patient's acute hepatitis evolved into acute liver failure with low-grade encephalopathy, markedly elevated transaminases, bilirubin, and impaired hepatic synthetic function. He was eventually diagnosed with acute hepatitis E virus (HEV) and was transitioned to supportive management. Acute HEV is a rare cause of acute liver failure. Hence, this case highlights the importance of early consideration of HEV in all patients with acute hepatitis who have originated from endemic regions.